Rancang Bangun Kwh Meter Digital Menggunakan Internet of Things - Rafi, Rio Guntur Dany; Supriyono, Supriyono; Zaenurrohman, Zaenurrohman; Purwiyanto, Purwiyanto (P3M Politeknik Negeri Cilacap, 2023)
In general, the kWh meter is installed in a distribution substation that supplies electrical energy to the building. The weakness of ordinary kWh meters cannot provide real information on electricity consumption. Measuring and recording the use of electrical energy still requires human power. By utilizing an internet network based on the Internet of Things (IoT) concept, this research aims to design and manufacture a digital kWh meter to monitor and control the use of electrical energy in buildings in real-time on a website. Using the website and the MYSQL-PHPMyAdmin Database as data storage. The PZEM-004T sensor is used to measure the electrical energy used, then it is processed on the Wemos D1 Mini microcontroller. From the test results that have been carried out, the digital Kwh meter has succeeded in monitoring and controlling the use of electrical energy through the website in real-time. Percentage average error value: voltage: 0.44% - 0.49%, current: 0.36%, cos phi leading: 39%, cos phi lagging: 1%, power: 0.93% - 2.68%, kWh: 16.3%, frequency: 0 %.